A Follow-Up Meta-analysis for Word-Problem-Solving Interventions for Students with Mathematics Difficulties - Zhang, Dake; Xin, Yan Ping (The Journal of educational research (Washington, D.C.), 2012)
Following a meta-analysis study conducted by Y. P. Xin and A. Jitendra ( 1999 ), the authors carried out a follow-up meta-analysis of word problem-solving interventions published from 1996 to 2009 for students with learning problems in mathematics. The authors examined the influence of education reforms as moderator variables on intervention effects, including inclusive movement, response to intervention model, standard movement, and mathematics education reform. The researchers analyzed 29 group-design studies and 10 single-subject-design studies that met the criteria for inclusion. Separate analyses were performed for group-design studies and single-subject studies using standardized mean change and percentage of nonoverlapping data (PND), respectively. The overall mean-weighted effect size (d) and PND for word problem-solving instruction were positive across the group-design studies (d = 1.848) and single-subject studies (PND = 95%). Implications for policymakers and researchers were discussed within the contexts of inclusive education, standard based movement, the response to intervention model, and mathematics education reform.